1999
DOI: 10.1136/bmj.318.7175.23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of open peer review on quality of reviews and on reviewers' recommendations: a randomised trial

Abstract: Resumen. Los procesos de evaluación de las revistas académicas y científicas se han transformado en los últimos años debido al incremento tanto del número de revistas como del volumen de artículos recibidos. Además, el uso de internet ha generado un fuerte aperturismo de la ciencia, con cada vez más revistas en acceso abierto. Los equipos editoriales han tenido que adaptarse y decidirse por un modelo de evaluación que se adecue a este nuevo entorno. Dado este contexto, en este artículo se expone el caso partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
266
1
12

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(288 citation statements)
references
References 8 publications
9
266
1
12
Order By: Relevance
“…Reviewer anonymity, meanwhile, is presumed to protect reviewers from undue influence, allowing them to give candid feedback without fear of possible reprisals from aggrieved authors. Various studies have failed to show that such measures increase review quality, however ( Fisher et al , 1994; Godlee et al , 1998; Justice et al , 1998; McNutt et al , 1990; van Rooyen et al , 1999). As Godlee and her colleagues have said, “Neither blinding reviewers to the authors and origin of the paper nor requiring them to sign their reports had any effect on rate of detection of errors.…”
Section: Discussion: the Traits Of Open Peer Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviewer anonymity, meanwhile, is presumed to protect reviewers from undue influence, allowing them to give candid feedback without fear of possible reprisals from aggrieved authors. Various studies have failed to show that such measures increase review quality, however ( Fisher et al , 1994; Godlee et al , 1998; Justice et al , 1998; McNutt et al , 1990; van Rooyen et al , 1999). As Godlee and her colleagues have said, “Neither blinding reviewers to the authors and origin of the paper nor requiring them to sign their reports had any effect on rate of detection of errors.…”
Section: Discussion: the Traits Of Open Peer Reviewmentioning
confidence: 99%
“…Proponents of open identity peer review argue that it will enhance accountability, further enable credit for peer reviewers, and simply make the system fairer: “most importantly, it seems unjust that authors should be “judged” by reviewers hiding behind anonymity” ( van Rooyen et al , 1999). Open identity peer review is argued, moreover, to potentially increase review quality, as it is theorised that reviewers will be more highly motivated and invest more care in their reviews if their names are attached to them.…”
Section: Discussion: the Traits Of Open Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to its detractors, open review may thus result in worse reports compared 137 to blind review, but this has not been observed in randomized, controlled trials [10,11,27]. 138…”
Section: Pros and Cons Of Open Pre-publication Peer Review 116mentioning
confidence: 99%
“…This trial was repeated on a larger scale by Justice et al (1998) and Van Rooyen et al (1999), with neither study finding that blinding reviewers improved the quality of reviews. These studies also showed that blinding is difficult in practice, as many manuscripts include clues on authorship.…”
Section: The Traits and Trends Affecting Modern Peer Reviewmentioning
confidence: 99%